The EAMENA database and its potential impact on research and heritage management: a case study of Crusader heritage in Lebanon - ten Harkel, A; Fisher, MT (Routledge, 2021)
This paper introduces the EAMENA database, from a user perspective, as a living document of archaeological datasets, assessing its utility for research and heritage management with respect to unfinished data collection and ongoing database development. An incomplete dataset of Crusader sites provides a useful case study of heritage places. First, through a simple analysis using the site function field, the paper demonstrates how users can query the database to identify areas or themes for future research. Second, it analyses condition assessments of Crusader sites in Lebanon to investigate whether these places are disproportionally affected by certain types of modern disturbance. Throughout, the paper discusses aspects of the EAMENA data recording process, highlighting several technical developments that the project has implemented since the public launch of its database in 2017. In doing so, it demonstrates the value of responsive database development to remain at the cutting edge of research technologies.